Pengaruh Locus Of Control Dan Reward Terhadap Kinerja Karyawan PT. Bank Negara Indonesia, Tbk. Kantor Cabang Harmoni - Wahyu Al Amin; Udin Saprudin (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research aims to examine and analyze the influence of Locus of Control on Employee Performance, Reward on Employee Performance, and Locus of Control and Reward simultaneously (together) on Employee Performance at PT. Bank Negara Indonesia, Harmoni Branch Office, Background Employee performance is a key determinant of a company's success. At PT. Bank Negara Indonesia, Tbk., Harmoni Branch Office, employee performance evaluations for the 2022-2024 period show fairly good results but still require improvement efforts. Furthermore, attendance data indicates a significant number of employee absences, especially in 2023, suggesting an issue that could affect performance. This problem is suspected to be influenced by internal employee factors such as Locus of Control and also management policies such as the provision of Reward. Methodology The research method used is quantitative descriptive with a survey approach. Data was obtained through the distribution of questionnaires to respondents and analyzed using multiple linear regression analysis with the aid of the SPSS version 27 program. Results t-test results indicate that Locus of Control has a positive and significant influence on Employee Performance, evidenced by the calculated t-value (t count = 7.556) being greater than the t-table value (t table = 1.980) and the significance value (0.000) being less than 0.05. Reward is also proven to have a positive and significant influence on Employee Performance. F-test results indicate that Locus of Control and Reward simultaneously have a positive and significant influence on Employee Performance. Overall, Locus of Control and Reward are proven to significantly influence Employee Performance at PT. Bank Negara Indonesia, Harmoni Branch Office, Central Jakarta. The contribution of influence from these two independent variables to Employee Performance is 32.8% (R² = 0.328), while the remaining 67.2% is influenced by other variables outside this study.